Effects of microbial fermentation on enzyme activity and volatile properties of Massa Medicata Fermentata. Issue 1 (30th November 2021) - Wang, Zitai; Okutsu, Kayu; Yoshizaki, Yumiko; Futagami, Taiki; Tamaki, Hisanori; Maruyama, Takuro; Toume, Kazufumi; Komatsu, Katsuko; Hashimoto, Fumio; Takamine, Kazunori
ABSTRACT: Aim: Massa Medicata Fementata (MMF) is a crude drug used in East Asia to treat anorexia and dyspepsia. It is prepared from wheat and several herbs through microbial fermentation using Aspergillus sp. and Rhizopus sp. There is great difference in the quality of commercial MMF, and the microbes of MMF are suggested to affect its quality. We investigated the effects of microbial fermentation on the quality of MMF. Methods: Raw materials of MMF were mixed according to the ratio listed in the National Standard for Chinese Patent Drugs, and MMF was prepared using pure cultures of Aspergillus oryzae or Rhizopus oryzae . Digestive enzyme activities (α‐amylase, protease, and lipase) and volatile compounds were measured using an analytical kit and GC–MS, respectively. Results: Enzyme activity increased in MMF. MMF prepared with A . oryzae (MMF‐A) showed higher α‐amylase and lipase activities than that prepared with R . oryzae (MMF‐R). Protease activity was marginally higher in MMF‐R than in MMF‐A. GC–MS analysis revealed that terpenoids decreased with fermentation; however, 2, 3‐butanediol, acetoin, and guaiacol were detected in MMF only. C8 compounds such as 1‐octen‐3‐ol were higher in MMF‐A than MMF‐R; however, aromatic compounds such as 4‐vinylguaiacol and pyrazines were higher in MMF‐R than MMF‐A. Conclusion: Microbial fermentation contributes to increased enzyme activity and changes in MMF volatiles. These properties of MMF were considerably affected by the microbes used, and it is proposed in this study that it is important to have microbial control in the production of commercial MMF.